Exploring Emergent Semantic Communities from DBLP Bibliography Database - Zhixing Huang; Yan Yan; Yuhui Qiu; Shuqiong Qiao (2009 International Conference on Advances in Social Network Analysis and Mining : 20-22 July 2009, 2009)
In this paper, we construct a word association network from DBLP bibliography records and detect its evolution progress based on community discovery algorithm CPM and CPMw. We found that the network is of complex network characteristics, and the detected semantic communities can be classified into two categories: giant community and small community. They differ in size and content, and behave differently in the network evolution. Discovering the evolution of network and the emergent semantic communities can help researchers grasp the state of arts of the related field, identify emergent issues and thus inspire new idea to solve scientific questions.